2011
DOI: 10.1093/ndt/gfr256
|View full text |Cite
|
Sign up to set email alerts
|

Effect of captopril treatment on recuperation from ischemia/reperfusion-induced acute renal injury

Abstract: At the acute stage of renal ischemia/reperfusion-induced AKI, ACE inhibition substantially contributed to the amelioration of acute injury by improving renal function, inhibiting systemic and intrarenal angiotensin-II, attenuating intrarenal inflammation and preserving renal tissue structure. Later on, at the post-reperfusion stage, most of the beneficial effects of captopril administration on the recuperating post-ischemic kidney were no longer evident. Concurrently, ACE inhibition exacerbated intrarenal hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 40 publications
4
50
0
1
Order By: Relevance
“…An unexplored area is the potential therapeutic benefit of shunting the RAS pathway from activation of angiotensin II receptor type 1 by angiotensin II to activation of the Mas receptor by angiotensin 1-7. Pretreatment with angiotensin-converting enzyme inhibitors, angiotensin receptor blockers, and aliskiren has been shown to mitigate renal ischemia-reperfusion injury in experimental models, primarily by reduction in postreperfusion inflammation (66)(67)(68). Additionally, one study reported a reduction in the severity of AKI at 48 hours postreperfusion when captopril was continuously administered through an intraperitoneal osmotic micropump implanted immediately after renal ischemia-reperfusion injury.…”
Section: Angiotensinogenmentioning
confidence: 99%
“…An unexplored area is the potential therapeutic benefit of shunting the RAS pathway from activation of angiotensin II receptor type 1 by angiotensin II to activation of the Mas receptor by angiotensin 1-7. Pretreatment with angiotensin-converting enzyme inhibitors, angiotensin receptor blockers, and aliskiren has been shown to mitigate renal ischemia-reperfusion injury in experimental models, primarily by reduction in postreperfusion inflammation (66)(67)(68). Additionally, one study reported a reduction in the severity of AKI at 48 hours postreperfusion when captopril was continuously administered through an intraperitoneal osmotic micropump implanted immediately after renal ischemia-reperfusion injury.…”
Section: Angiotensinogenmentioning
confidence: 99%
“…[6][7][8] The pathogenesis of AKI is complex, however, it has been shown that ischemia/reperfusion triggers AKI, mainly via aggravating stresses, inflammation and activation of renin-angiotensin system (RAS). 9 Hypoxia, serum deprivation and oxidative stress are important factors in the pathogenesis of AKI. [10][11][12] As mentioned before, MSC transplantation could treat AKI; however, the most important problem with the application of MSCs for the treatment is their low survival rate in such a stressful microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…34 In another study, cystatin-C levels were found higher in rats where ischemia was formed experimentally compared to the control group and the group receiving treatment. 35 In our study, cystatin-C values were determined to be significantly lower in pneumoperitoneum + theophylline group. These our results show similarity to the studies performed previously in the literature.…”
mentioning
confidence: 43%